THE ANTIBIOTICS RESISTANCE AND THE PRESCRIPTIONS’ PATTERN FOR URINARY TRACT INFECTIONS AT KING FAHAD SPECIALIST HOSPITAL - RA LNQER, NORAH; AL JASSER, AREEJ; A. MOBARK, MUGAHID (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Urinary tract infection (UTI) is one of the diseases with a highest prevalence in the world. This study evaluated the antibiotics resistant and the prescription pattern for UTI with the aim to participate as an effective monitoring study that enhances rational antibiotics’ prescription. Methods: We conducted a retrospective cross-sectional study at King Fahad Specialist Hospital from May 2018 to January 2019. We included a total of 306 patients with UTI. 204 patients diagnosed clinically and empirically treated (Group A), 102 patients underwent urine for culture and sensitivity tests (Group B). Results: UTI showed higher occurrence in female in both Groups A (61%) and B (65%). The mean age was higher in Group B (55.8 years) than Group A (39.44 years). The most commonly prescribed antibiotics for UTI were Trimethoprim + Sulfamethoxazole (TMP+SMX) (56%) and ciprofloxacin (15%). Escherichia coli was the most commonly isolated organism (36.3%) followed by Klebsiella pneumonia (30%). Although 41.17% of organisms were sensitive to TMP+SMX, 38.2% were resistant to it. The organisms were sensitive to amikacin in 80.4% and to gentamicin in 61.8% whereas, 61.8% were resistant to ampicillin. Luckily, no resistance was reported neither for nitrofurantoin nor for vancomycin. Conclusion: The study showed significant resistance to the commonly prescribed TMP+SMX and ciprofloxacin compared to absolute sensitivity to the less prescribed nitrofurantoin. This necessitates special consideration for local susceptibility in empirical therapy.